Racial/Ethnic Differences in Poststroke Rehabilitation Outcomes. (15th June 2014) - Ellis, Charles; Hyacinth, Hyacinth I.; Beckett, Jamie; Feng, Wuwei; Chimowitz, Marc; Ovbiagele, Bruce; Lackland, Dan; Adams, Robert
Abstract : Background . Significant racial and ethnic disparities in stroke incidence, severity, and morbidity have been consistently reported; however, less is known about potential differences in poststroke rehabilitation outcomes. Objective . To examine racial and ethnic differences in poststroke rehabilitation outcomes. Methods . We completed an in-depth search of Medline and several major journals dedicated to publishing research articles on stroke, rehabilitation, and racial-ethnic patterns of disease over a 10-year period (2003–2012). We identified studies that reported rehabilitation outcomes and the race or ethnicity of at least two groups. Results . 17 studies involving 429, 108 stroke survivors met inclusion criteria for the review. The majority (94%) of studies examined outcomes between Blacks and Whites. Of those studies examining outcomes between Blacks and Whites, 59% showed that Blacks were generally less likely to achieve equivalent functional improvement following rehabilitation. Blacks were more likely to experience lower FIM gain or change scores (range: 1–60%) and more likely to have lower efficiency scores (range: 5–16%) than Whites. Conclusions . Black stroke survivors appear to generally achieve poorer functional outcomes than White stroke survivors. Future studies are warranted to evaluate the precise magnitude of these differences, whether they go beyond chance, and the underlying contributory mechanisms.